Biomass Novel Adsorbents for Phenol and Mercury Removal - Nabais, Joao Manuel Valente (2022)
Funding Information: The authors are thankful to FCT (Portugal), COMPETE, QREN, and EU (European Regional Development Fund, FEDER) for financial support through Project FCOMP-01-0124-FEDER-007142. S. Román thanks the Agencia Española de Investigación for the financial help through project PID2020-116144RB-I00/AEI/10.13039/501100011033.